2016
DOI: 10.13080/z-a.2016.103.002
|View full text |Cite
|
Sign up to set email alerts
|

Winter oilseed rape and weed competition in organic farming using non-chemical weed control

Abstract: One of the reasons why the area sown with oilseed rape in organic farms is not expanding is problems with weed, disease, and pest control as well as low seed yield. There is a lack of investigations on oilseed rape cultivated in an organic system, especially employing innovative weed control methods. To fill this gap in knowledge, field experiments were conducted at the Experimental Station of Aleksandras Stulginskis University in 2012-2013 with the aim of identifying and assessing the impact of different non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Researchers have indicated that thermal weed control is more effective than mechanical weed control (Virbickaitė et al, 2006;Ascard et al, 2007). However, other researches came up with opposite conclusions (Velička et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Researchers have indicated that thermal weed control is more effective than mechanical weed control (Virbickaitė et al, 2006;Ascard et al, 2007). However, other researches came up with opposite conclusions (Velička et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…A major problem that organic farmers face is weed management (Edesi et al, 2012). In most organic farms, weeds are controlled mechanically (Jodaugienė et al, 2008;Van der Weide et al, 2008;Fontanelli et al, 2009;Pannacci, Tei, 2014). Another increasingly used weed control method is thermal weed control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant yielding depends on a large number of factors that are often correlated with each other and directly or indirectly affect the yield of a given plant. Soil factors (pH, structure, organic matter content, nutrient level), weather and climatic factors (air temperature, rainfall, insolation), soil tillage technologies, plant varieties, technology and fertilization level, plant protection, harvesting technology as well as crop rotation can be taken into account the most often (Khairunniza-Bejo et al 2014;Velička et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, this is associated with intense fertilization and the application of large amounts of pesticides, which may negatively impact the consumer. It is thus essential to develop and improve edible oil production systems to make them both satisfying to the farmer and non-threatening to the consumer (Velicka et al, 2016). Fertilizer applications, especially on nutrient deficient soils, can therefore increase crop yields and quality (Albert et al, 2012;Malhi, 2012).…”
Section: Introductionmentioning
confidence: 99%